Does migration network matter in driving internal migration in Indonesia? - Novriawati, Erma; Nasrudin, Rus'an (Jurnal Ekonomi & Studi Pembangunan, 2023)
Migration theory has developed a framework that considers factors influencing migration, including the pursuit of better economic opportunities in the destination area, which is a crucial pull factor. However, the internal migration literature, especially in Indonesia, currently lacks empirical evidence to show the role of migration networks as a mediating element in this mechanism. To address this research gap, we conducted a case study in Indonesia to examine the role of the migration network on the decision process of internal migrants. Our findings show that migration networks matter in driving internal migration with a moderate size effect, implying informational factors beyond those provided by networks also play a crucial role in migration decisions. These results indicate the importance of exploring additional avenues to enhance the positive impact of migration networks, such as creating designated social media applications to facilitate connections among potential migrants or exploring alternative means of meaningful engagement. Further research should examine the efficacy of such interventions and their potential to augment the influence of migration networks on migration decisions.